Advances in drag-reduction methods related with boundary layer control – A review. (2021) - Kumar, Susheel; Pandey, Krishna Murari; Sharma, Kaushal Kumar
Abstract: In our day to day life we see the phenomenon of turbulence everywhere, and it is one of the main reasons in loss of energy. We all know about the energy crisis our world is facing and the global warming problem planet earth is facing, so there is an urgent need to decrease our energy consumption and for that increasing efficiency is one of a key factor. One of the major part in turbulence is the viscous force that occurs between any two boundaries be it solid–liquid or solid–gas boundary. The friction force which occurs in turbulence greatly decreases the efficiency, so decreasing the friction forces can significantly improves the efficiency. In his paper boundary layer control methods which can help in drag reduction are reviewed. Methods such as polymer additives, super hydrophobic surfaces, air bubbles drag reduction, morphology drag reductions composite drag reductions were reviewed along with their applications in various fields is discussed. Finally some new ideas are presented to improve the current drag reduction techniques.